2019
DOI: 10.3390/s19112593
|View full text |Cite
|
Sign up to set email alerts
|

Precise Point Positioning Using World’s First Dual-Frequency GPS/GALILEO Smartphone

Abstract: The release of the world’s first dual-frequency GPS/Galileo smartphone, Xiaomi mi 8, in 2018 provides an opportunity for high-precision positioning using ultra low-cost sensors. In this research, the GNSS precise point positioning (PPP) accuracy of the Xiaomi mi 8 smartphone is tested in post-processing and real-time modes. Raw dual-frequency observations are collected over two different time windows from both of the Xiaomi mi 8 smartphone and a Trimble R9 geodetic-quality GNSS receiver using a short baseline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Nevertheless, the authors still believe that the smartphone appears fully capable of supporting centimeter-level carrier phase differential GNSS positioning. In recent years, as more smartphones are equipped with a dual frequency GNSS chip, in addition to differential positioning method [ 5 , 6 , 7 , 8 , 9 ] the precise point positioning (PPP) method is also used in GNSS high-precision positioning of smartphones [ 10 , 11 , 12 ]. PPP is a precision absolute point positioning technology based on state space domain correction information with international GNSS service (IGS) products [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the authors still believe that the smartphone appears fully capable of supporting centimeter-level carrier phase differential GNSS positioning. In recent years, as more smartphones are equipped with a dual frequency GNSS chip, in addition to differential positioning method [ 5 , 6 , 7 , 8 , 9 ] the precise point positioning (PPP) method is also used in GNSS high-precision positioning of smartphones [ 10 , 11 , 12 ]. PPP is a precision absolute point positioning technology based on state space domain correction information with international GNSS service (IGS) products [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPP is a precision absolute point positioning technology based on state space domain correction information with international GNSS service (IGS) products [ 13 , 14 ]. The GPS/Galileo pseudorange and carrier phase observations L1/L5 and E1/E5 of Xiaomi Mi 8 were used in the ionosphere-free combined PPP mathematical model [ 11 ], and the experimental results showed that the dual frequency GNSS smartphone is capable of achieving decimeter-level positioning accuracy. Wu et al [ 12 ] compared Xiaomi Mi 8 and geodetic receiver from the perspective of single frequency and dual frequency PPP models, the experimental results showed that the positioning accuracy of dual frequency PPP with ionosphere-free combination on Xiaomi Mi 8 is similar to the geodetic receivers in single frequency PPP mode.…”
Section: Introductionmentioning
confidence: 99%
“…In outdoor environments, Global Navigation Satellite System (GNSSs)—e.g., Global Positioning System (GPS), Globalnaya Navigazionnaya Sputnikovaya Sistema (GLONASS), Galileo, and BeiDou [ 13 ]—are widely adopted for global positioning purposes [ 14 , 15 ]; i.e., GNSS is supposed to provide accurate positioning anywhere on Earth. The GPS accuracy, in terms of positioning error, in smartphones is usually within a 4.9 m radius in clear open sky conditions, but it is capable of centimeter accuracy when it is used in combination with dual-frequency receivers and/or augmentation systems [ 16 , 17 ]. Despite the high accuracy and global coverage provided by GNSSs, they cannot properly operate indoors.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting distressed humans from the developed aerial rescue system has mainly relied on GNSS techniques. Notable research has been conducted for the GNSS precise point positioning (PPP) accuracy of portable devices such as smartphones, tested in both post-processing and real-time modes [11,12,13]. The results of their positioning performance assessment compared to the geodetic receivers’ ones indicate that the utilization of multi GNSS systems data can effectively improve positioning performance, which is essential for missions in marine environments.…”
Section: Introductionmentioning
confidence: 99%